A Case Study of Energy-Saving and Frost Heave Control Scheme in Artificial Ground Freezing Project. (3rd June 2022) - Zhang, Song; Zhou, Xiao-min; Zhang, Jiwei; Sun, Tiecheng; Ma, Wenzhu; Liu, Yong; Yang, Ning
Abstract : In large-scale shallow buried artificial ground freezing (AGF) engineering, frost heave control and energy-saving have always been the most critical problems. By the research and analysis, this manuscript points out the applicability and superiority of intermittent freezing in large-scale shallow buried freezing projects and conducts in situ tests for the freezing project of a metro entrance. The test results show that intermittent freezing can effectively control the surface frost heave, but it has a certain hysteresis. The freezing wall thickness, average temperature, and optimization scheme during the freezing process are discussed. The results show the following: (1) Intermittent freezing would degrade the thickness of the freezing wall and the average temperature together. (2) The stop freezing scheme in intermittent freezing is not fit to frost heave control during the excavation stage. Therefore, it is necessary to establish a freezing cycle scheme with precise temperature control to control the frost heave to ensure the bearing capacity. Based on the above conclusions, a dual-circuit liquid supply scheme, the specific brine temperature control scheme, and its application method were proposed. Through this method, the development process of the freezing front can be effectively controlled, and the goal of being precise and controllable can be achieved. This research can provide practical technical guidance for frost heave control of similar AGF projects.